Is Standardization Transferable? Initial Experience of Urethral Surgery at the University Hospital Frankfurt - Wenzel, Mike; Krimphove, Marieke J.; Lauer, Benedikt; Hoeh, Benedikt; Müller, Matthias J.; Mandel, Philipp; Becker, Andreas; Vetterlein, Malte W.; Mueller, Stefan C.; Dahlem, Roland; Fisch, Margit; Chun, Felix K.-H.; et al. (Frontiers in Surgery, 2020)
Background: Since January 2018 performance of urethroplasties is done on regular basis at the University Hospital Frankfurt (UKF). We aimed to implement and transfer an institutional standardized perioperative algorithm for urethral surgery (established at the University Hospital Hamburg-Eppendorf—UKE) using a validated Urethral Stricture Surgery Patient-Reported Outcome Measure (USS-PROM) in patients undergoing urethroplasty at UKF. Materials and Methods: We retrospectively analyzed all patients who underwent urethroplasty for urethral stricture disease between January 2018 and January 2020 at UKF. All patients were offered to revisit for clinical follow-up (FU) and completion of USS-PROM. Primary end point was stricture recurrence-free survival (RFS). Secondary endpoints were functional outcomes, quality of life (QoL), and patient satisfaction. Results: In total, 50 patients underwent urethroplasty and 74 and 24% had a history of previous urethrotomy or urethroplasty, respectively. A buccal mucosal graft urethroplasty was performed in 86% (n = 43). After patient's exclusion due to lost of FU, FU <3 months, and/or a pending second stage procedure, 40 patients were eligible for final analysis. At median FU of 10 months (interquartile-range 5.0–18.0), RFS was 83%. After successful voiding trial, the postoperative median Qmax significantly improved (24.0 vs. 7.0 mL/s; p < 0.01). Conversely, median residual urine decreased significantly (78 vs. 10 mL; p < 0.01). Overall, 95% of patients stated that QoL improved and 90% were satisfied by the surgical outcome. Conclusions: We demonstrated a successful implementation and transfer of an institutional standardized perioperative algorithm for urethral surgery from one location (UKE) to another (UKF). In our short-term FU, urethroplasty showed excellent RFS, low complication rates, good functional results, improvement of QoL and high patient satisfaction. PROMs allow an objective comparison between different centers.